Analisis Status Gizi Dalam Perkembangan Kemampuan Kognitif Anak Usia 3-4 Tahun Di Desa Nyawangan Kras Kediri - Prassasty, Anna; Hajjar Sujani, Elfara; Irsad Rusdiani, Nurtina (AL IHSAN: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
The aim of this study is to analyze the relationship between nutritional status and cognitive development in children aged 3-4 years in Nyawangan Village, Kras District, Kediri Regency. This research is based on the early childhood period as a critical stage for cognitive development, which is highly influenced by nutritional status, while nutritional problems in toddlers remain a challenge in rural areas. This study uses a qualitative approach with a case study type to gain an in-depth and holistic understanding. Data were collected through qualitative study techniques including participant observation, in-depth interviews, and documentation studies involving 9 parents with 3 different nutritional statuses each and 3 community health post (posyandu) cadres. The results of the study showed that children with good nutritional status have more advanced cognitive abilities related to language, problem-solving, and concept recognition compared to children with poor nutritional status or at risk of stunting. The findings of this study reveal that nutritional status is not a standalone entity, but is highly influenced by parenting patterns, feeding practices, as well as the socio-economic context and the level of parental knowledge